Navigating the Tides of Change: A Comprehensive Analysis of Employment and Unemployment Dynamics in Indonesia - Nico Pranata Mulya (Cognitionis Civitatis et Politicae, 2024)
An essential component of a nation's economic development is labor dynamics. The purpose of this study is to perform a descriptive analysis of Indonesia's unemployment and working population comparison between 2011 and 2020. The information utilized comes from BPS statistical records and includes the number of employed and unemployed individuals as well as auxiliary variables like employment opportunities, wage rates, economic growth, and educational attainment. The primary trends in the workplace over the last ten years are examined in this study using a descriptive analysis methodology. The impact of multiple factors, such as the global economic crisis, technological advancements, and the unprecedented pandemic, was examined by analyzing notable shifts in the unemployment rate and working population. Key determinants of employment dynamics include things like economic growth, institutional policies, structural transformation, and educational attainment. This research contributes significantly to our understanding of the intricate dynamics of employment in Indonesia and sheds light on policy implications for inclusive growth, better jobs, and labor market resilience. It is anticipated that the implications of this study will provide a basis for the development of policies that are more flexible and sensitive to upcoming difficulties, resulting in the establishment of an employment environment that is both inclusive and sustainable.